2020
DOI: 10.3389/fneur.2020.572589
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome and Prognosis After Thrombectomy in Patients With Concomitant Malignancy

Abstract: Endovascular thrombectomy (EVT) is the preferred treatment strategy for patients with acute ischemic stroke (AIS). However, clinical outcome and prognosis in patients who undergo EVT in response to AIS with concomitant malignancy have not been fully elucidated. Data of patients with malignancy who underwent EVT at participating institutions between January 2015 and April 2019 were retrospectively analyzed. Patient characteristics, treatment methods, posttreatment strategy, and long-term prognosis were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…All of the included studies were retrospective analyses of either files/databases of patients that received acute treatment for AIS [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], or analyses of hospital records with the use of diagnostic codes, e.g., ICD codes for AIS and malignancy [ 20 , 21 , 22 ]. One study was a retrospective analysis of cancer patients from the MR CLEAN thrombectomy study registry [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the included studies were retrospective analyses of either files/databases of patients that received acute treatment for AIS [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], or analyses of hospital records with the use of diagnostic codes, e.g., ICD codes for AIS and malignancy [ 20 , 21 , 22 ]. One study was a retrospective analysis of cancer patients from the MR CLEAN thrombectomy study registry [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was a certain amount of discrepancy regarding the patients included in the studies. Most studies included patients with AIS and an active malignancy (AM), defined as patients with a diagnosis of current or metastatic cancer, those undergoing treatment for cancer, or who refused the treatment [ 6 , 7 , 10 , 11 , 13 , 14 , 15 , 16 , 18 , 24 ], and at times patients with a diagnosis made during or after the AIS-hospitalization [ 10 , 14 , 15 ]. This definition was occasionally restricted to a diagnosis within a year or 6months, or cancer treatment within 1–6 months of the ischemic event [ 7 , 11 , 18 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, stroke affects mortality in patients with active cancer by various ways including the termination of malignancy treatment and the worsening of general conditions. Moreover, Oki et al showed that 92% of patients with cancer-related stroke died within 1 y after the stroke occurred [ 17 ]. In cancer patients, thromboembolism and progression of cancer are major causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [12] Jung et al [13] Cho et al [14] Sallustio et al [15] Jeon et al [16] Oki et al [17] Present report cases in which MT cannot be performed in consideration of risks and benefits. However, this study lacks consideration for these cases, including only the cases where MT was performed.…”
Section: Authorsmentioning
confidence: 96%
See 1 more Smart Citation